INTERPOL 90TH GENERAL ASSEMBLY AND THE SECURITISATION OF BETTER POLICE COOPERATION WITH NATIONAL CENTRAL BUREAU JAKARTA - Sirait, Marcellino L P; Putranti, Ika R; Susiatiningsih, Hermini (Global: Jurnal Politik Internasional, 2023)
In the modern age, the police institution is utilised as the primary spearhead to combat multiple sources of possible disruptions for the general safety of the public. The Indonesian National Police (INP) as a member of the INTERPOL takes part in multitude of activities conducted by the international organization. Currently, the Indonesian National Police is facing a rising number in the cases of missing persons, unidentified remains and crimes against children with casualties not only from Indonesian nationalities, but also international citizens. The current shortcoming of national technicalities and mechanism may open up a structured and tangible operational help from the INTERPOL in order to increase the efficiency and efficacy of police investigation in Indonesia. This research employs the securitization theory and qualitative method of analysis, along with field research and desk research respectively. Analysis shows that the Indonesian National Police is in favor of the agenda proposed by the INTERPOL during the 90th INTERPOL General Assembly, specifically to increase operational quality of member states, while also supporting the securitization process by the INTERPOL before and during the 90th General Assembly.